2017
DOI: 10.1111/wrr.12524
|View full text |Cite
|
Sign up to set email alerts
|

Foxn1 and Mmp‐9 expression in intact skin and during excisional wound repair in young, adult, and old C57Bl/6 mice

Abstract: The transcription factor Foxn1 is essential for skin development. Our previous studies performed on young C57BL/6J mice model showed that Foxn1 acts as regulator of the skin wound healing process. The present study extended our initial research regarding the expression and potential role of Foxn1 in the intact and wounded skin as a function of animal age and stage of the wound healing process. We analyzed Foxn1 and Mmp-9 expression in the intact and postinjured skin of young, adult, and old C57BL/6J and transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 27 publications
3
49
0
7
Order By: Relevance
“…Furthermore, the large differences in body mass gain between young FOXN1 þ/þ mice and young FOXN1 eGFP/þ mice and the less prominent differences in old mice may reflect the age-related downregulation of FOXN1 expression. The decrease in FOXN1 expression was detected in old (21 months of age) mice; we did not observe this phenomenon in our previous experiments employing 16-to 18-month-old mice (Kopcewicz et al, 2017). This observation is consistent with research on the thymus that showed a decrease in FOXN1 expression with age and concomitant age-related thymic involution (Chen et al, 2009;Ortman et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, the large differences in body mass gain between young FOXN1 þ/þ mice and young FOXN1 eGFP/þ mice and the less prominent differences in old mice may reflect the age-related downregulation of FOXN1 expression. The decrease in FOXN1 expression was detected in old (21 months of age) mice; we did not observe this phenomenon in our previous experiments employing 16-to 18-month-old mice (Kopcewicz et al, 2017). This observation is consistent with research on the thymus that showed a decrease in FOXN1 expression with age and concomitant age-related thymic involution (Chen et al, 2009;Ortman et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, our previous and present data suggest that the transcription factor FOXN1 acts as a pro-scarring factor in the skin wound healing process. We observed scarless skin healing in FOXN1-deficient mice (Gawronska-Kozak et al, 2006), participation of FOXN1 in re-epithelialization and epithelial to mesenchymal transition during skin wound healing, (Gawronska-Kozak et al, 2016;Kopcewicz et al, 2017) and its stimulatory role in skin adipogenesis (present data). A decrease in FOXN1 expression with age coincided with scarless skin healing observed in older individuals (Ashcroft et al, 2002), which additionally underlines the role of FOXN1 in mouse and possible human skin wound healing processes.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations